Aging, exceptional longevity and comparisons of the Hannum and Horvath epigenetic clocks. (May 2017) - Armstrong, Nicola J; Mather, Karen A; Thalamuthu, Anbupalam; Wright, Margaret J; Trollor, Julian N; Ames, David; Brodaty, Henry; Schofield, Peter R; Sachdev, Perminder S; Kwok, John B
Aim: To examine the relationships between two epigenetic clocks, aging and exceptional longevity.Materials & methods: Participants were from three adult cohorts with blood DNA methylation data (Illumina 450 K, n = 275, 34–103 years). Epigenetic age (DNAmage) and age acceleration measures were calculated using the Hannum and Horvath epigenetic clocks.Results: Across all cohorts, DNAmage was correlated with chronological age. In the long-lived cohort (Sydney Centenarian Study; 95+, n = 23), DNAmage was lower than chronological age for both clocks. Mean Sydney Centenarian Study Hannum age acceleration was negative, while the converse was observed for the Horvath model.Conclusion: Long-lived individuals have a young epigenetic age compared with their chronological age.